2012
DOI: 10.1002/jhm.1959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased overnight supervision on resident education, decision‐making, and autonomy

Abstract: BACKGROUND: New supervisory regulations highlight the challenge of balancing housestaff supervision and autonomy. To better understand the impact of increased supervision on residency training, we investigated housestaff perceptions of education, autonomy, and clinical decisionmaking before and after implementation of an in-hospital, overnight attending physician (nocturnist).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 12 publications
(11 reference statements)
1
79
0
1
Order By: Relevance
“…With both increased off-hours supervision in our hospital and increasing use of faculty-level physicians in other academic programs, these results provide context for the anticipated level of overnight housestaff supervision. 26,27 To our knowledge, this is the first study to investigate perceived overnight quality issues on medicine units following such staffing models. Although this model of direct, on-site supervision in academic medicine programs may help offset staffing and supervisory issues during off hours, the nocturnist role is insufficient to offset threats to quality/safety already inherent within the system.…”
Section: Discussionmentioning
confidence: 99%
“…With both increased off-hours supervision in our hospital and increasing use of faculty-level physicians in other academic programs, these results provide context for the anticipated level of overnight housestaff supervision. 26,27 To our knowledge, this is the first study to investigate perceived overnight quality issues on medicine units following such staffing models. Although this model of direct, on-site supervision in academic medicine programs may help offset staffing and supervisory issues during off hours, the nocturnist role is insufficient to offset threats to quality/safety already inherent within the system.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] While night float rotations have been valued for their experiential learning potential, they have historically lacked a formalized educational component. 8,9 As trainees now spend an increasing amount of time on night float rotations, residency programs have evolved to leverage the potential learning opportunities available at night and to establish new metrics to define its success.…”
Section: Introductionmentioning
confidence: 99%
“…At night, residents have fewer administrative tasks, affording additional time for formal education. 9 Challenges inherent in night float rotations include cross-coverage responsibilities and resident fatigue, leading to decreased alertness. 10 Two studies 2,3 showed perceived improvements in the value of care delivered and in resident education with the presence of dedicated, on-site, attending physicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper by Haber et al, increased overnight supervision enhanced the clinical value of the night float rotation, increased rates of attending contact during critical clinical decision-making, and improved perception of patient care. 3 Nighttime supervision is a key concept in medical education and is critical in ensuring safe and effective patient care. 4 As noted by Hanson et al, nighttime education should be transformed in a way that maintains clinical productivity for both attending and resident physicians, integrates high-quality teaching and curricula, and achieves a balance between patient safety and resident autonomy.…”
mentioning
confidence: 99%